Analisis Terhadap Proses Penyimpanan Rekam Medis Elektronik di Rumah Sakit Islam Jakarta Sukapura - Safitro, Ario (JATISI, 2025)
Technological developments in the health sector are an effort to accelerate equity and reduce health service disparities. The implementation of SIMRS is very important to integrate all services offered by hospitals, one of which is electronic medical records (RME). This study aims to analyze the process of storing Electronic Medical Records (RME) at the Jakarta Islamic Hospital (RSIJ) Sukapura based on the principles of data and information security in accordance with the Regulation of the Minister of Health Number 24 of 2022 concerning Medical Records. This study uses a qualitative descriptive method with data collection techniques through observation, in-depth interviews, and literature studies. The results of the study show that RSIJ Sukapura does not have a special policy that specifically regulates the storage of electronic medical records by guaranteeing the principles of data and information security which include the principle of confidentiality, the principle of integrity, and the principle of availability. In addition, the storage capacity that is assessed has not met the storage standard for at least 25 years and does not have a backup system outside the hospital. This study suggests updates, adjustments and policy making to ensure optimal and regulatory RME storage.